A compact, friction self-matching, non-inertial piezo motor with scanning capability. (1st May 2023) - Zhao, Kesen; Hou, Yubin; Zheng, Shaofeng; Wang, Jihao; Lu, Yalin; Meng, Wenjie; Lu, Qingyou
Abstract: Maintaining friction matching is the core issue for non-inertial piezo motors (PMs); this challenge severely limits their application in complex conditions such as variable temperature environments. To address this issue, a compact, optimal friction self-matching PM with non-inertial driving is reported in this paper. The motor is implemented with a narrow 5.5 mm-outer diameter piezoelectric scanner tube (PST) whose outer electrode is equally divided into two independently controllable PSTs. The PST, divided into two parts, clamps a sapphire rod between dual sapphire ball structures at both ends and an elastically supported sapphire ball at the centre. The device features a balanced normal force distribution scheme that allows friction forces acting on the sapphire rod at both ends and on the intermediate section to be approximately equal along the axial direction of the PST, achieving automatic optimal matching of friction, then it can operate like an inchworm motor. The feasibility of this scheme is verified by testing with a low threshold voltage down to 35 V at room temperature and 160 V at liquid nitrogen temperature. The motor dimensions are 5.5 mm × 5.5 mm ×35 mm (length × width × height). At room temperature, step size ranges from 0.1 μ m to 1 μ m. It has a maximum stroke about 5 mm and a maximum load of 40 g. This PM's extreme compactness, low machine tolerance requirements, and smooth sequence make it ideally suited for building superior quality, atomically resolved scanning probe microscopy devices compatible with narrow spaces and extreme conditions.